Non-game like training benefits spoken foreign-language processing in children with dyslexia - Junttila, Katja; Smolander, Anna-Riikka; Karhila, Reima; Kurimo, Mikko; Ylinen, Sari (Frontiers in Human Neuroscience, 2023)
Children with dyslexia often face difficulties in learning foreign languages, which is reflected as weaker neural activation. However, digital language-learning applications could support learning-induced plastic changes in the brain. Here we aimed to investigate whether plastic changes occur in children with dyslexia more readily after targeted training with a digital language-learning game or similar training without game-like elements. We used auditory event-related potentials (ERPs), specifically, the mismatch negativity (MMN), to study learning-induced changes in the brain responses. Participants were 24 school-aged Finnish-speaking children with dyslexia and 24 age-matched typically reading control children. They trained English speech sounds and words with “Say it again, kid!” (SIAK) language-learning game for five weeks between ERP measurements. During the game, the players explored game boards and produced English words aloud to score stars as feedback from an automatic speech recogniser. To compare the effectiveness of the training type (game vs. non-game), we embedded in the game some non-game levels stripped of all game-like elements. In the dyslexia group, the non-game training increased the MMN amplitude more than the game training, whereas in the control group the game training increased the MMN response more than the non-game training. In the dyslexia group, the MMN increase with the non-game training correlated with phonological awareness: the children with poorer phonological awareness showed a larger increase in the MMN response. Improved neural processing of foreign speech sounds as indicated by the MMN increase suggests that targeted training with a simple application could alleviate some spoken foreign-language learning difficulties that are related to phonological processing in children with dyslexia.